Editorial: Enhancing Natural Regeneration to Restore Landscapes - Lohbeck, M.; Rother, D.C.; Jakovac, C.C. (Frontiers Media, 2021)
With this Research Topic we aimed to advance our understanding of how natural regeneration can effectively contribute to achieve restoration goals by compiling evidence on (1) processes that drive natural regeneration at the regional scale, and their consequences for spatially prioritizing natural regeneration as a restoration strategy, (2) successional processes driving recovery, (3) how management can enhance natural regeneration to achieve restoration targets, and (4) how external factors shape the restoration potential of natural regeneration.